Preparing effective illustrations. Part 1: graphs - Ng, K.H.; Peh, W.C.G. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
Illustrations (also known as figures) are visual representations of the results obtained from a scientific study. Graphs are a common type of illustration that are often used in scientific papers to present information clearly and effectively, as well as to demonstrate relationships between variables in the data. Graphs also serve to reveal trends or patterns in the data. This article provides some basic guidelines to assist authors in preparing effective graphs for their papers.